Protocol For Electronic Digital Signature of Asymmetric The Importance of Age Characteristics in Working with Primary School Students - O‘rmonova Mahdiyabonu Xosiljon qizi; Olimova Nilufar Qosimjon qizi (Zien Journals, 2022)
In educational process there are several key factors critical to the efficiency of the lessons conducted. Among them it is important to take into account the age characteristics of junior school children. The following article is devoted to the physical and psychological qualities of elementary school children so that the teachers can identify appropriate approach for individual class members
Keywords: crisis; visual-figurative thinking; imagination; emotional communication